Embedded sensor for detecting corrosion of reinforcement in concrete - Ismail, Mohammad (Trans Tech Publications, 2011)
Corrosion of reinforcement is a worldwide problem which causes premature degradations in reinforced concrete structures. Monitoring reinforcement corrosion in concrete can be achieved by embedding corrosion sensor within the concrete cover. In this research, capacitance-based embedded sensor was developed to monitor corrosion potential (Ecorr) and corrosion rate (Icorr) parameters of reinforcement continuously. The sensors were tied to the reinforcement and embedded in concrete slab specimens followed by immersion into NaCl solution for 70 days. During this period, corrosion parameters were weekly recorded. At the same time, half-cell corrosion testing using Portable SRI-CMIII was conducted for calibration purpose. From the research, it was observed that the patterns of Ecorr and Icorr shown by the embedded sensors were similar to that of portable SRI-CMIII device - an indication of suitability of the embedded sensor towards sensing existing corrosion activities around the embedded steel bars. Eventually, the bars were found corroded from the broken specimens to confirm the detection of corrosion activities as recorded by the sensors.